Electronic data collection to enhance disease surveillance at the slaughterhouse in a smallholder production system - Falzon, Laura C.; Ogola, Joseph G.; Odinga, Christian O.; Naboyshchikov, L.; Fèvre, Eric M.; Berezowski, J. (Springer, 2021)
Globally, meat inspection provides data for animal health surveillance. However, paper-based recording of data is often not reported through to higher authorities in sufficient detail. We trialled the use of an electronic meat inspection form in Kenyan slaughterhouses, in lieu of the currently used paper-based format. Meat inspectors in two ruminant slaughterhouses completed and submitted an electronic report for each animal slaughtered at their facility. The reports, which captured information on the animal demographics and any eventual condemnations, were stored in a central database and available in real-time. A stakeholder meeting was held towards the end of the study. Over the 2.75 year study period, 16,386 reports were submitted; a downward linear trend in the monthly submissions was noted. There was a week effect, whereby more reports were submitted on the market day. Of the slaughtered animals, 23% had at least a partial condemnation. The most frequently condemned organs were the liver, lungs and intestines; the primary reasons for condemnations were parasitic conditions. Lack of feedback and difficulty capturing animal origin information were the primary challenges highlighted. The study demonstrated that electronic data capture is feasible in such challenging environments, thereby improving the timeliness and resolution of the data collected.